Decomposition of salix and populus leaves in standard class “A” evaporation pans - Kucserka, Tamás; Simon, Brigitta; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2018)
Decomposition and evaporation are both basic measures of aquatic ecosystems, nevertheless they are rarely studied compared to each other. A research was carried out with four class “A” evaporation pans.  One of them was filled with water (control pan), while the other three with sediment from Lake Balaton, on which leaf litter bags were placed. Decomposition rate and daily evaporation were measured in the pans. Leaf mass losses followed the exponential decay curve, decomposition rates were in the fast category. Water temperature in the pans was driven by air temperature. Among the meteorological elements, the daily average air temperature greatly influences the evaporation values, the rate of evaporation increases with warming.
Keywords: leaf litter decomposition; Salix; Willow; class “A” pan